Macroeconomics: An Overview of Key Concepts and Policies - Grace Felipa (International Journal of Science and Society, 2023)
This scientific journal article provides an in-depth analysis of macroeconomics, focusing on its fundamental concepts and policies. Macroeconomics is a vital field in economics that examines the behavior of an entire economy, studying factors like aggregate production, unemployment, inflation, and economic growth. This article aims to shed light on the key principles governing macroeconomic phenomena and the policies employed to stabilize and improve economic conditions. By understanding macroeconomics, policymakers can make informed decisions to foster sustainable economic development.